RESEARCH OF PHYSICAL AND CHEMICAL PROPERTIES OF ICE-CREAM FROM CATNES MILK - A. U. Shingisov; M. K. Alimardanova; R. B. Mukhtarkhanova; U. U. Tastemirova (Алматы технологиялық университетінің хабаршысы, 2021)
The article presents the results of the study of physicochemical properties, photographs of ash and spectrograms of the mineral composition of ice cream from cow and mare's milk, obtained on an ICP-MC mass spectrometer. It has been established that the values of the hydrogen activity index (pH) in ice cream based on mare's milk are less by 0.09 compared to the value of ice cream from cow's milk, and also in ice cream from mare's milk of weakly bound moisture more than in ice cream from cow's milk. Research has established that prototypes of mare milk ice cream are not inferior to traditional cow milk ice cream in terms of their physicochemical properties and mineral content, and surpass the latter in some mineral elements (calcium, phosphorus, selenium, iron and aluminum).